Research on the mechanics of CFRP composite lap joints - Curnutt, Austin (Kansas State University, 2017)
For this thesis, research was performed on CFRP bonded composite lap-joints with one and two continuous laminas through the lap. Composite wraps used to retrofit existing structures use lap joints to maintain their integrity. The use of composites for retrofitting structures has many advantages over traditional methods, such as steel jacketing, and is becoming more widely accepted in the structural engineering industry. While much literature exists documenting the performance of composite wraps as a whole when applied to concrete columns, less information is available on the behavior of the lap-joint of the wrap. Developing a better understanding of how the lap-joint behaves will help researchers further understand composite column wraps. This research sought to determine what affect continuous middle laminas may have on the stiffness of lap joints and whether or not stress concentrations exist in the lap-joint due to a change in stiffness.
Keywords: CFRP; Lap-joint; Carbon fiber reinforced polymer